2016
DOI: 10.1007/s40808-016-0098-6
|View full text |Cite
|
Sign up to set email alerts
|

Fusing of optimized intelligence models by virtue of committee machine for estimation of the residual shear strength of clay

Abstract: Owing to high dependency of landslide stability to residual shear strength (RSS) of clay, provide a sophisticated strategy for modeling of this parameter is advantageous. This paper present strategy based upon fusing of optimized intelligence models for estimation of RSS of clay as a function of readily available data. The developed model is achieved through implementing two following steps. In the first step, two optimized models including optimized neural network, and optimized fuzzy logic are developed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Mamdani and Sugeno are two types of the fuzzy inference system that are known for their capability. In solving regression problems by the fuzzy inference system, one of the important tasks that impact model accuracy is finding the optimum values for membership functions (Asoodeh et al 2014a;Asoodeh et al 2015;Gholami & Bodaghi 2016;Ahmadi et al 2017). In this study, the Bat-inspired algorithm was merged with the fuzzy inference system for achieving the best value of membership function, which is in the structure of Sugeno, therefore furthering its ability to map the functional dependency between the longitudinal dispersion coefficient and its influencing parameters.…”
Section: Optimized Fuzzy Inference Systemmentioning
confidence: 99%
“…Mamdani and Sugeno are two types of the fuzzy inference system that are known for their capability. In solving regression problems by the fuzzy inference system, one of the important tasks that impact model accuracy is finding the optimum values for membership functions (Asoodeh et al 2014a;Asoodeh et al 2015;Gholami & Bodaghi 2016;Ahmadi et al 2017). In this study, the Bat-inspired algorithm was merged with the fuzzy inference system for achieving the best value of membership function, which is in the structure of Sugeno, therefore furthering its ability to map the functional dependency between the longitudinal dispersion coefficient and its influencing parameters.…”
Section: Optimized Fuzzy Inference Systemmentioning
confidence: 99%
“…However, it has been found that the radial basis function is a better kernel to be used in regression problems. Since the influence of penalty parameters of support vector regression on the performance of a constructed model is greatly high, it is considered as one of the most challenging issues while training the model. Thus, finding the values of these parameters plays a key role in successfully applying this method for solving knotty problems. In this study, BA was combined with support vector regression to improve its efficiency by calculating the optimum value of free parameters while OSVR was constructed in the MATLAB environment.…”
Section: Model Descriptionmentioning
confidence: 99%